Presence of microplastics in shipwrecks along the continental shelf of the state of Pernambuco - Brazil - de Oliveira, Jéssica Cristina Mendes; Hilborne, Benjamin Alfie; Vilas Boas, Dinabel Alves Cirne; da Silva Rodrigues, Midiã; Banja Fernandes, Múcio Luiz; da Silva, Andrea Karla P.; Pereira, Artur Torquato (International journal of environmental studies, 2024)
This study analyses the microplastics in the sediment of areas surrounding shipwrecks on the Continental Shelf of Pernambuco, North eastern Brazil. The sediment collection was carried out around six wrecks. Flotation methodology was used to separate the possible microplastics from the sediment. Microplastics were classified by type and colour. Of the 6 shipwrecks analysed, 413 microplastic items were identified, with nylon fibre predominating. Fibres of blue colour were the most frequent, totalling 48.4%. The presence of microplastics in shipwrecks shows that this environment, even far from the coast, is subject to human activity. The accumulation of microplastics in the sediments surrounding the shipwrecks may pose a risk to marine life.